Probiotics in medicine - Małgorzata Szamocka; Monika Anna Ameryk; Maciej Świątkowski (Kazimierz Wielki University, 2017)
Technical and technological progress has changed the production methods of agricultural products and has decreased the overall production costs. Eager reliance on chemical agents and genetic engineering has led to the emergence of risks concerning even traditional food products. Therefore, it is becoming increasingly common to return to the traditional production methods involving the use of biological agents, with the aim to restore a healthy lifestyle and sustainability. This requires a new approach and new solutions developed cooperatively by "soil doctors", i.e. farmers and environmental scientists, vets and medical doctors. Human health is a reflection of the health of the ecosystem. Fertile soil is essential for the health of plants, animals and humans. Probiotics, prebiotics, bacteriophages and plant extracts exhibit a vast potential as natural technologies that are environment-, animal- and human-friendly. Probiotics are live microorganisms that, if used in proper quantities, favorably affect health. In order for a microorganism to be named a probiotic, a series of tests has to be run to confirm its safety, resistance to difficult conditions in the gastrointestinal tract and a clearly beneficial impact on health. The location and activity of probiotics is mainly associated with the large intestine. The beneficial effect of probiotics depends on the strain and dose. The most important of their actions is maintaining homeostasis of the intestinal microflora, which prevents diseases of the gastrointestinal tract and contributes to well-being. The correct balance in the quantity of microorganisms is crucial for host defense and sustained health. Clinical and experimental studies provide evidence of the effectiveness of using probiotics in both prophylaxis and treatment of many diseases. However, further research is necessary to confirm the effects of probiotics and, perhaps by means of genetic engineering, to select new strains endowed with clinically confirmed probiotic properties and free of adverse reactions.